No evidence of Zika, dengue, or chikungunya virus infection in field-caught mosquitoes from the Recife Metropolitan Region, Brazil, 2015 [version 1; peer review: 2 approved] - Anita Ramesh; Claire L. Jeffries; Priscila Castanha; Paula A. S. Oliveira; Neal Alexander; Mary Cameron; Cynthia Braga; Thomas Walker (Wellcome Open Research, 2019)
Background: The Recife Metropolitan Region (RMR), north-eastern Brazil, was the epicentre of the 2015 Zika virus (ZIKV) epidemic, which was followed by a 2016 chikungunya virus (CHIKV) epidemic. It historically has amongst the highest incidence of dengue virus (DENV) infections and is the only remaining focus of lymphatic filariasis (LF) in Brazil. In early 2015, a molecular xenomonitoring surveillance project focused on Culex (Cx.) quinquefasciatus commenced to inform LF elimination activities. Aedes (Ae.) aegypti mosquitoes were also collected, concurrent with the first microcephaly cases detected in the RMR. In terms of the 2015 ZIKV epidemic, these are the earliest known field-collected mosquitoes, preserved for potential RNA virus detection, when ZIKV was known to be circulating locally. Methods:   Adult mosquitoes were collected in two sites (0.4 km2) of Sítio Novo, Olinda, RMR, from July 22 to August 21, 2015. Mosquitoes were morphologically identified, sorted by physiological status, and pooled (up to 10 mosquitoes per house per day or week). RNA was extracted, reverse transcribed and the cDNA tested by real-time PCR. Results: A total of 10,139 adult female Cx. quinquefasciatus and 939 adult female Ae. aegypti were captured. All female Ae. aegypti specimens were included within 156 pools and screened for ZIKV, DENV and CHIKV. In addition, a sub-set of 1,556 Cx. quinquefasciatus adult females in 182 pools were screened for ZIKV. No evidence of infection with any of the three arboviruses was found. Conclusions: The absence of arbovirus detection may have been expected given the extremely restricted geographic area and collection of mosquitoes during a very short time period of peak mosquito abundance (July–September), but low arbovirus circulation (November–March).  However, this study demonstrates the potential to retrospectively screen for additional unexpected pathogens in situations of rapid emergence, such as occurred during the outbreak of ZIKV in the RMR.